Differential cytokine levels between early withdrawal and remission states in patients with alcohol dependence. (February 2017) - Yen, Che-Hung; Ho, Pei-Shen; Yeh, Yi-Wei; Liang, Chih-Sung; Kuo, Shin-Chang; Huang, Chang-Chih; Chen, Chun-Yen; Shih, Mei-Chen; Ma, Kuo-Hsing; Sung, Yueh-Feng; Lu, Ru-Band; Huang, San-Yuan
Highlights: Inflammation and cognitive impairment were observed in AD patients, however these conditions can be improved by early abstinence from alcohol. Levels of circulating cytokines, liver function, and cognitive function may markers of alcohol use disorder. Total abstinence is the best option to prevent alcohol induced inflammatory responses and cognitive impairment. Abstract: Alcohol dependence (AD) leads to altered innate and adaptive immune responses, and frequently co-occurs with inflammation. Therefore, inflammatory cytokines potentially play a crucial role in the development of alcohol-related illnesses. This study evaluated changes in plasma cytokine concentrations, liver function, cravings, depression severity, and cognitive function in male patients with AD, during the course of an alcohol-detoxification program. A total of 78 male patients with AD were recruited for a conservative detoxification program; and cytokine levels, depressive score, and cognitive impairment applying the Trail Making Test (TMT) were evaluated during early withdrawal (baseline) and after 4 weeks of abstinence from alcohol. Healthy volunteers (86 males) were also recruited as controls. Inflammatory cytokine expression in all participants was assessed by multiplex magnetic bead assay. AD patients during early withdrawal demonstrated higher cytokine levels than the healthy controls ( P ≤ 0.001 for all cytokines). However, the levels of cytokine expression were significantly lower after 4 weeks of abstinence from alcohol ( P ≤ 0.001, except for IL-1β and IL-5). Higher liver function marker levels, depressive severity, and TMT times were observed in patients at the beginning of the detoxification program than in healthy controls. Fortunately, these functions significantly ameliorated after 4 weeks of abstinence. ( P ≤ 0.001). Levels of circulating cytokines, liver function, and cognitive function may markers of alcohol use disorder.